2021
DOI: 10.33425/2639-8478.1059
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of Colorectal Cancer (CRC) in Oman

Abstract: Introduction: Colorectal cancer (CRC) is the first most predominant malignancy in men, a bit less 3rd commonest in women. The prevalence rate is higher in developed than in developing economies, though the pattern is gradually changing. In Oman, CRC prevalence rate has shown a significant escalating pattern in the recent past. From 1996 to 2012, CRC incidence in Oman has increased by 282% in females and 386% in males. There is emerging data that right and left sided lesions are different in terms of aetiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These findings support those reported by previous studies conducted in Oman and neighboring countries which indicate that CRC in this region of the world is diagnosed at a younger age and more advanced stage compared to Western populations, particularly if patients are obese, overweight, or have existing comorbidities such as diabetes. [24][25][26] With regards to the functional scale of the EORTC QLQ-CR29, the mean score for body image in this study was high (88.9), while those for weight (79.3) and anxiety (75.4) were satisfactory. Previous studies conducted in nearby countries such Saudi Arabia, Jordan, and Egypt have shown that Arab CRC patients demonstrate similarly high scores in terms of functioning.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These findings support those reported by previous studies conducted in Oman and neighboring countries which indicate that CRC in this region of the world is diagnosed at a younger age and more advanced stage compared to Western populations, particularly if patients are obese, overweight, or have existing comorbidities such as diabetes. [24][25][26] With regards to the functional scale of the EORTC QLQ-CR29, the mean score for body image in this study was high (88.9), while those for weight (79.3) and anxiety (75.4) were satisfactory. Previous studies conducted in nearby countries such Saudi Arabia, Jordan, and Egypt have shown that Arab CRC patients demonstrate similarly high scores in terms of functioning.…”
Section: Discussionmentioning
confidence: 60%
“…These findings support those reported by previous studies conducted in Oman and neighboring countries which indicate that CRC in this region of the world is diagnosed at a younger age and more advanced stage compared to Western populations, particularly if patients are obese, overweight, or have existing comorbidities such as diabetes. 24 26 …”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a foremost global health concern and remains one of the major causes of cancer-related morbidity and mortality in both developed and developing countries (14) . It is the third most common cancer in adults after lung cancer and breast cancer worldwide.…”
Section: Discussionmentioning
confidence: 99%